Meditation in a New York minute [compact disc] : super calm for the super busy - Thornton, Mark (Meditation expert) (Sounds True, 2006)
Mark Thornton demystifies meditation and makes it accessible to all. He presents his complete program for enjoying the many benefits of meditation. They include stress reduction, energy, and intense mental clarity.